2018
DOI: 10.3390/smartcities1010005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Smart Sustainable City Development: Implications for Project Management

Abstract: Projects and project management (PM) are becoming a way of working, and many changes in society have evolved because of projects. However, will the societal agenda also influence the project management discipline? Societal issues generated by urban population growth and rapid urbanization arise in cities. Making a city “smart” and sustainable is emerging as a strategy to mitigate these issues. How does this development impact project management? In order to answer this question, we performed meaningful learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…[10] As a result of the literature review and previous studies technological economic systems are not implemented in cities according to the time line that mentioned for their appearance [3], but to the vision of the city, needs and moves to smartness. [11] As shown in figure 1 and also it was found that there is dynamic and overlap between technological economic types. It is possible to appear more than one type of technological economics in one city.…”
Section: Economic Growth and Technologymentioning
confidence: 85%
“…[10] As a result of the literature review and previous studies technological economic systems are not implemented in cities according to the time line that mentioned for their appearance [3], but to the vision of the city, needs and moves to smartness. [11] As shown in figure 1 and also it was found that there is dynamic and overlap between technological economic types. It is possible to appear more than one type of technological economics in one city.…”
Section: Economic Growth and Technologymentioning
confidence: 85%
“…Schipper and Silvius [ 38 ] looked at the characteristics of smart sustainable city development and the implications for project management. They stated that cities may require a centralised and comprehensive approach to strike an appropriate balance between diverse service exploration in different domains and intensive service exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that cities may require a centralised and comprehensive approach to strike an appropriate balance between diverse service exploration in different domains and intensive service exploitation. Publicly driven partnerships may help to accelerate smart city adoption at an early stage [ 38 ]. In the case of Croatian smart cities, Milenković et al [ 39 ] showed how the government’s role in public–private partnership projects is to evaluate and approve detailed execution plans of the concessionaire while the private partner’s role is to design, build, finance, and operate the facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The paper specifically deals with the topic of application of program management in the process of smart city development. Program management includes the phase of preparation and definition of the program, program goals, defining the time frame of required resources and costs and analysis of the expected effects of the program, to make a decision on the justification of the program (Schipper, & Silvius, 2018). Planning of time and resources for each project, summarizing plans in a central place, consolidation of plans into a program plan, analysis of potential conflicts between projects (especially resource), decision making, revision of project plans, project implementation, monitoring and program control, are the following steps (Gareis, 2005).…”
Section: Program Managementmentioning
confidence: 99%